2009
DOI: 10.1017/s0022112009007198
|View full text |Cite
|
Sign up to set email alerts
|

Drop impact of yield-stress fluids

Abstract: International audienceThe normal impact of a drop of yield-stress fluid on a flat rigid surface is investigated experimentally. Using different model fluids (polymer microgels, clay suspensions) and impacted surfaces (partially wettable, super-hydrophobic), we find a rich variety of impact regimes from irreversible viscoplastic coating to giant elastic spreading and recoil. A minimal model of inertial spreading, taking into account an elasto-viscoplastic rheology, allows explaining in a single framework the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
167
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(184 citation statements)
references
References 52 publications
16
167
1
Order By: Relevance
“…This means that bulk rheological properties and not surface tension are responsible for the arrest of the spreading in our study. In a previous work [16], we have shown that for a soft yield-stress fluid like Carbopol, elasticity controls the impact dynamics even above the yield stress, because the impact time is much shorter than the fluid relaxation time (large Deborah numbers). In Fig.…”
Section: Giant Drag Reduction In Complex Fluid Drops On Rough Hydrophmentioning
confidence: 95%
See 1 more Smart Citation
“…This means that bulk rheological properties and not surface tension are responsible for the arrest of the spreading in our study. In a previous work [16], we have shown that for a soft yield-stress fluid like Carbopol, elasticity controls the impact dynamics even above the yield stress, because the impact time is much shorter than the fluid relaxation time (large Deborah numbers). In Fig.…”
Section: Giant Drag Reduction In Complex Fluid Drops On Rough Hydrophmentioning
confidence: 95%
“…The first one is the capillary length scale =V 2 0 . The second is a viscous length scale defined as L 0 =Re [24], where Re is an effective Reynolds number of the Carbopol drops computed from the steady-state rheology of the fluid [16]. Figure 3(c) shows a good collapse of the data when is normalized by the capillary length scale, that is, using a Weber number based on the roughness size: V 2 0 = ¼ ð=L 0 ÞWe.…”
Section: Prl 110 184501 (2013) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 96%
“…In particular, a symmetric copper rod impact is computed and compared to the experimental data provided in [9]. Then, a low velocity clay suspension impact is studied and compared to the experimental results obtained in [19].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, it has become possible to explore in unprecedented detail the influence of a wide range of physical parameters on various stages of drop impact and to systematically compare experiment and theory 5,[13][14][15][16] . For instance, the splashing transition in Newtonian fluids was found to be set by atmosphere pressure 5 , while the intrinsic rheology decides the spreading dynamics of yield-stress fluids 17 .…”
Section: Introductionmentioning
confidence: 99%